Achieving Near‐unity Photoluminescence Quantum Yields in Organic‐Inorganic Hybrid Antimony (III) Chlorides with the [SbCl5] Geometry. (25th January 2023) - Sun, Chen; Deng, Zeyu; Li, Zhiyuan; Chen, Zhongwei; Zhang, Xuanyu; Chen, Jian; Lu, Haipeng; Canepa, Pieremanuele; Chen, Rui; Mao, Lingling
Abstract: Hybrid organic–inorganic antimony halides have attracted increasing attention due to the non‐toxicity, stability, and high photoluminescence quantum yield (PLQY). To shed light on the structural factors that contribute to the high PLQY, five pairs of antimony halides with general formula A 2 SbCl5 and A 2 Sb2 Cl8 are synthesized via two distinct methods and characterized. The A 2 SbCl5 type adopts square pyramidal [SbCl5 ] geometry with near‐unity PLQY, while the A 2 Sb2 Cl8 adopts seesaw dimmer [Sb2 Cl8 ] geometry with PLQY≈0 %. Through combined data analysis with the literature, we have found that A 2 SbCl5 series with square pyramidal geometry generally has much longer Sb⋅⋅⋅Sb distances, leading to more expressed lone pairs of Sb III . Additional factors including Sb−Cl distance and stability of antimony chlorides may also affect PLQY. Our targeted synthesis and correlated insights provide efficient tools to precisely form highly emissive materials for optoelectronic applications. Abstract : Five pairs of antimony chlorides have been synthesized via two synthetic conditions to produce distinctively different structures and PL properties. The A 2 SbCl5 types with square pyramidal [SbCl5 ] geometry and near‐unity PLQY can be synthesized via diffusion method in DMF. Alternatively, when growing via solution method in HCl, the non‐emissive A 2 Sb2 Cl8 types with seesaw dimmer geometry are obtained.